Changing of ancestor worship in the Confucian patrilineal descent group in Vietnam: The case of Ho Chi Minh city - NGUYEN THI HOAI CHAU (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: This research aims to better understand the unique aspects of Vietnamese ancestor veneration. Ancestor worship in Vietnam is the subject of this study, which focuses on the largely unmentioned relationship with Confucianism, specifically the filial piety concept based on the patrilineal bloodline.Methodology: Methods like interviews were used extensively in Ho Chi Minh City’s fieldwork research, with a focus on a small neighborhood populated by people from the north, where more traditional values prevail.Findings: Thus, for instance, the son preference was a clear expression of the Confucian ancestor worship based on Confucianism’s patrilineal bloodline. In addition, this study aims to shed light on the evolution of ancestor worship by analyzing traditional characteristics and their connection to Vietnam’s historical context, all against the backdrop of the many influential factors undergoing rapid change today.Novelty/Implications: This research sets out to draw attention to a recent shift in the way Vietnamese celebrate their dead. Ancestral worship in Vietnam is a topic of current and future study, and the shift in emphasis away from the Confucian concept of patrilineal lineage is a key factor.